2016
DOI: 10.1155/2016/5803893
|View full text |Cite
|
Sign up to set email alerts
|

A Biogeography-Based Optimization Algorithm Hybridized with Tabu Search for the Quadratic Assignment Problem

Abstract: The quadratic assignment problem (QAP) is an NP-hard combinatorial optimization problem with a wide variety of applications. Biogeography-based optimization (BBO), a relatively new optimization technique based on the biogeography concept, uses the idea of migration strategy of species to derive algorithm for solving optimization problems. It has been shown that BBO provides performance on a par with other optimization methods. A classical BBO algorithm employs the mutation operator as its diversification strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Findings of their study revealed that the proposed algorithm was less time consuming and outperformed other methods in terms of solving real-life instances and random instances with high quality. In order to solve the QAP, Lim et al (2016) proposed another hybrid algorithm which is formed by combining the Biogeography-Based Optimization Algorithm and Tabu Search. With the use of the proposed hybrid algorithm, the best solutions were found for 36 instances out of 37 instances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Findings of their study revealed that the proposed algorithm was less time consuming and outperformed other methods in terms of solving real-life instances and random instances with high quality. In order to solve the QAP, Lim et al (2016) proposed another hybrid algorithm which is formed by combining the Biogeography-Based Optimization Algorithm and Tabu Search. With the use of the proposed hybrid algorithm, the best solutions were found for 36 instances out of 37 instances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By means of abstracting a species migration mechanism in different islands, these Biogeography-based optimization methods mimic the distribution of the species in natural biogeography. The island in the BBO [14] is not only a small piece of land surrounded by water but an area that is isolated geographically. In biogeography, the quality of geographical areas can be judged by taking various elements into consideration that include humidity, temperature, and climate.…”
Section: Proposed Biogeography-based Optimization (Bbo) -Adhoc On-mentioning
confidence: 99%
“…However, an application of BBO algorithm for machine layout design problems to minimize the material handling distance is described by Sooncharoen et al (2015). A hybrid technique is proposed combining BBO and TS algorithms to solve QAP and obtained better results within reasonable computational time by Lim et al (2016). Regarding multi-objective BBO, some of its applications are depicted here.…”
Section: Application Of Bbo and Nsbbo From Literaturementioning
confidence: 99%